P104 Pharmacologic differences of adalimumab, infliximab and etanercept: do we need specific vaccination recommendations for prenatally exposed infants?. Issue 6 (17th May 2019) - Welzel, T; Gotta, V; Rakhmanina, N; van den Anker, JN
Abstract : Background: In pregnancy adalimumab (ADA) and infliximab (IFX) should preferentially be stopped at gestational week 20 and etanercept (ETN) at weeks 30–32 1 because of their steadily increased transplacental transfer during the late second and third trimester. Pregnant women with chronic inflammatory diseases are often treated throughout their entire pregnancy to prevent negative impact on pregnancy outcomes from the disease. Therefore, more infants are born with prenatal exposure and the question arises if and when live vaccines can be administered safely. Methods: We reviewed pharmacologic properties of ADA, IFX and ETN with regards to prenatal exposure and vaccine recommendations. Results: IFX is a chimeric and ADA a human anti-TNF-alpha antibody. Both have high binding affinity to the neonatal Fc receptor (FcRn). 2 ETN is a TNF-alpha receptor fusion protein with a 5–10 fold lower binding affinity to the FcRn compared with IFX/ADA. 2 At delivery neonatal drug concentrations compared with maternal ones seem to be higher in prenatally exposed infants to IFX 3-5 (median ratio of 1.97) and ADA (median ratio of 1.21), 3 whereas neonatal ETN concentrations are lower. 6 7 The mean time to drug clearance in IFX or ADA exposed infants is 7.3 months and 4 months, respectively. 3 Drug concentrations are undetectable for IFX or ADA after 12 and 9 months of life, respectively. 3 In infants exposed throughout the entire pregnancy ETN is undetectable after 3 months. 7 Infants exposed to ADA, IFX and ETN before gestational week 22 can follow the normal vaccination schedule including live vaccines, 1 whereas live vaccines in infants exposed in the late second and third trimester should be avoided for 6–12 months of life. 1 3 Conclusion: Pharmacologic differences of ADA, ETN and IFX require specific live vaccine recommendations for infants exposed prenatally to these drugs. References: Götestam Skorpen C, Hoeltzenbein M, et al. The EULAR points to consider for use of antirheumatic drugs before pregnancy, and during pregnancy and lactation. Ann Rheum Dis 2016;75(5):795–810. Porter C, Armstrong-Fisher S, et al. Certolizumab pegol does not bind the neonatal Fc receptor (FcRn): Consequences for FcRn-mediated in vitro transcytosis and ex vivo human placental transfer. J Reprod Immunol 2016; 116:7–12. Julsgaard M, Christensen LA, et al. Concentrations of adalimumab and infliximab in mothers and newborns, and effects on infection. Gastroenterology 2016;151(1):110–9. Mahadevan U, Wolf DC, et al. Placental transfer of anti-tumor necrosis factor agents in pregnant patients with inflammatory bowel disease. Clin Gastroenterol Hepatol, 2013. 11(3):286–92;quiz e24. Zelinkova Z, de Haar C, et al. High intra-uterine exposure to infliximab following maternal anti-TNF treatment during pregnancy. Aliment Pharmacol Ther, 2011. 33(9):1053–8. Berthelsen BG, Fjeldsøe-Nielsen H, et al. Etanercept concentrations in maternal serum, umbilical cord serum, breast milk and child serum during breastfeeding. Rheumatology (Oxford) 2010; 49(11):2225–7. Murashima A, Watanabe N, et al. Etanercept during pregnancy and lactation in a patient with rheumatoid arthritis: drug levels in maternal serum, cord blood, breast milk and the infant´s serum. Ann Rheum Dis 2009; 68(11):1793–4. Disclosure(s): Nothing to disclose